Effects of SNR on the Accuracy and Reproducibility of DTI-derived Fractional Anisotropy, Mean Diffusivity, and Principal Eigenvector Measurements at 1.5T - Farrell, Jonathan A.D. (2007)
PURPOSE: To develop an experimental protocol to calculate the precision and accuracy of fractional anisotropy (FA), mean diffusivity (MD), and the orientation of the principal eigenvector (PEV) as a function of the signal to noise ratio (SNR) in vivo. MATERIALS AND METHODS: A healthy male volunteer was scanned in three separate scanning sessions, yielding a total of 45 DTI scans. To provide FA, MD, and PEV as a function of SNR, sequential scans from a scan session were grouped into non-intersecting sets. Analysis of the accuracy and precision of the DTI-derived contrasts was done in both a voxel-wise and ROI-based manner. RESULTS: An upward bias of FA and no significant bias in MD were present as SNR decreased, confirming results from simulation-based studies. Notably, while the precision of the PEV became worse at low SNR, no bias in the PEV orientation was observed. Overall, an accurate and precise quantification of FA values in GM requires substantially more SNR than the quantification of WM FA values CONCLUSION: This study provides guidance for FA, MD, and PEV quantification and a means to investigate the minimal detectable differences within and across scan sessions as a function of SNR.